Gel electrolyte membrane for lithium-sulfur battery, preparation method and energy storage device
By using a gel electrolyte membrane containing halogenated amide additives and monomers with unsaturated carbon-carbon double bonds and disulfide bonds in lithium sulfur batteries, the problems of shuttle effect and loss of active substances in lithium sulfur batteries are solved, and the circulation performance and safety of the battery are significantly improved.
Patent Information
- Application Number
- CN202411838454.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-13
AI Technical Summary
During the circulation process of lithium sulfur batteries, due to the solid-liquid-solid conversion mechanism of sulfur, lithium polysulfide is easily soluble in the electrolyte, causing shuttle effect and loss of active substances, thereby reducing the battery cycle life and safety.
A gel electrolyte membrane is used, including a base membrane and a polymer electrolyte based on base membrane curing. The polymer electrolyte raw materials include halogenated amide additives, monomers containing unsaturated carbon-carbon double bonds and disulfide bonds, ether solvents, lithium salts and initiators. A stable dissolution environment is provided through ether solvents, the introduction of monomers containing unsaturated carbon-carbon double bonds and disulfide bonds inhibits the shuttle effect, and promotes the dissolution and conversion of lithium polysulfide through halogenated amide additives.
It effectively inhibits the occurrence of "shuttle effect", avoids the consumption of positive and negative electrode active substances, and optimizes the electrochemical performance and circulation capabilities of lithium sulfur batteries.
Smart Images

Figure BDA0005187365940000151 
Figure BDA0005187365940000161 
Figure BDA0005187365940000171
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a gel electrolyte membrane for lithium-sulfur batteries, a preparation method and an energy storage device. Background Art
[0002] Lithium-ion batteries with graphite as negative electrodes are currently close to their theoretical energy density, but with the continuous development of battery technology, people have higher and higher requirements for high energy density batteries. Among them, lithium-sulfur batteries based on conversion reactions and lithium metal negative electrodes have extremely high theoretical specific capacity (1675mAh / g) and theoretical specific energy (2600Wh / kg). At the same time, sulfur reserves are abundant, low in price and environmentally friendly, so lithium-sulfur batteries have become one of the most promising battery solutions.
[0003] Since the active substance sulfur (S) in lithium-sulfur batteries undergoes a solid-liquid-solid conversion mechanism during the cycle, lithium polysulfides (LiPSs) are easily soluble in the electrolyte. The dissolved LiPSs easily shuttle to the negative electrode in the electrolyte and react irreversibly with lithium metal, resulting in the loss of active substances, that is, the "shuttle effect". At the same time, the active metal lithium negative electrode is prone to side reactions with the electrolyte and form dead lithium and lithium dendrites, which greatly reduces the battery cycle life and safety.
[0004] In lithium-sulfur batteries, the use of solid electrolytes instead of traditional liquid electrolytes can effectively inhibit the dissolution of LiPSs and interfacial side reactions, thereby alleviating the "shuttle effect" and inhibiting the growth of lithium dendrites. However, the ionic conductivity of organic polymer solid electrolytes is often insufficient at room temperature, while inorganic solid electrolytes have poor processability and formability, making them difficult to use in practice. One solution is to use gel polymers to replace solid electrolytes. However, although the use of gel polymer electrolytes can effectively inhibit the generation of the "shuttle effect", there is still a serious problem. Since gel polymer electrolytes usually include monomers such as polycarbonates and polyacrylic acids, most of these monomers will undergo irreversible chemical reactions with LiPSs, resulting in the loss of active substances. How to ensure that the gel polymer electrolytes inhibit the "shuttle effect" while avoiding the consumption of positive and negative active substances has become a major difficulty in current research. Summary of the invention
[0005] In order to solve the problems of the prior art, the present invention provides a gel electrolyte membrane for a lithium-sulfur battery, which suppresses the "shuttle effect" of LiPSs and avoids the consumption of positive and negative active materials, thereby optimizing the electrochemical performance and cycle capacity of the lithium-sulfur battery.
[0006] In a first aspect, the present invention provides a gel electrolyte membrane for a lithium-sulfur battery, comprising a base membrane and a polymer electrolyte solidified based on the base membrane, wherein the polymer electrolyte raw materials include a halogenated amide additive, a monomer containing unsaturated carbon-carbon double bonds and disulfide bonds, an ether solvent, a lithium salt, and an initiator.
[0007] On the second aspect, the present solution also proposes an energy storage device using a gel electrolyte membrane as a separator and / or a semi-solid electrolyte.
[0008] As a further solution, the energy storage device includes a battery cell.
[0009] As some preferred schemes, the halogenated amide additive is selected from chain halogenated amide additives having a terminal amide group and a halogen element substitution number less than or equal to 3.
[0010] As a further preferred scheme, the chain halogenated amide additive having a terminal amide group and a halogen element substitution number less than or equal to 3 can be further preferably a chain halogenated amide additive having a carbon chain length less than or equal to 6 and having a terminal amide group and a halogen element substitution number less than or equal to 3.
[0011] As a further preferred embodiment, the carbon chain length may be further preferably 4, and further, the carbon chain length may be further preferably 3, 2, or 1.
[0012] As some preferred schemes, the monomer containing unsaturated carbon-carbon double bonds and disulfide bonds is preferably a symmetrical monomer containing double-terminal unsaturated carbon-carbon double bonds and disulfide bonds.
[0013] As a further solution, the polymer electrolyte raw material may further include a halogenated sulfonamide additive.
[0014] As a further preferred embodiment, the halogenated sulfonamide may further preferably be a chain halogenated sulfonamide having a symmetrical structure.
[0015] As a further solution, the ether solvent is selected from any one or more of simple ether solvents, polyether solvents and cyclic ether solvents.
[0016] As a further solution, the lithium salt is selected from any one or more of organic lithium salts and inorganic lithium salts.
[0017] As a further embodiment, the organic lithium salt is selected from any one or more of fluorine-substituted lithium sulfonate salts, lithium oxalate salts and lithium borate salts.
[0018] As a further solution, the inorganic lithium salt is selected from any one or more of fluorine-substituted inorganic lithium borate salts, fluorine-substituted inorganic lithium phosphate salts, fluorine-substituted inorganic lithium chlorate salts, and inorganic lithium nitrate salts.
[0019] As a further embodiment, the initiator is selected from any one of ketone compounds and phosphorus oxides.
[0020] As a further solution, the polymer electrolyte raw material further includes a second solvent, and the second solvent is selected from any one or more of ester solvents or acetal solvents.
[0021] As a further solution, the ester solvent is selected from any one or more of chain carbonate solvents, carboxylic acid ester solvents, and phosphate ester solvents.
[0022] As a further solution, the mass ratio of the ether solvent to the second solvent in the gel electrolyte membrane is selected from 0.2 to 2.
[0023] As a further solution, the base film is selected from glass cellulose film, cellulose film and porous polyolefin compound film, and one or more layers of coating may be provided on the base film.
[0024] As a further solution, the coating is not limited in principle, and for example, can be selected from any one or more of polymer materials, carbon materials, and oxide materials.
[0025] As a further solution, the gel electrolyte membrane has a Raman spectrum of 512 cm -1 The Raman scattering peak at comes from SS, and the standard deviation of the peak position is 2 cm -1 Within.
[0026] In a third aspect, the present invention also proposes a method for preparing a gel electrolyte membrane, the specific steps of which are:
[0027] S1: Under an inert atmosphere, a lithium salt is dissolved in an ether solvent, a halogenated amide additive and a monomer containing an unsaturated carbon-carbon double bond and a disulfide bond are added, and then an initiator is added, and the mixture is mixed to obtain a precursor solution;
[0028] S2: In a dry environment, immerse the base film in the precursor solution, take it out after it is completely soaked, and irradiate it with ultraviolet light to obtain a gel electrolyte membrane.
[0029] As a further solution, in step S1, the inert atmosphere is selected from any one of helium, neon, argon, krypton, xenon, and radon.
[0030] As a further solution, in step S1, the total mass content of the lithium salt in the polymer electrolyte is selected from 5% to 50%.
[0031] As a further solution, in step S1, the total mass content of the lithium salt in the polymer electrolyte is selected from 10%-30%.
[0032] As a further solution, in step S1, the lithium salt concentration is selected from 0.1 mol / L-5 mol / L.
[0033] As a further solution, in step S1, the lithium salt concentration is selected from 1.5 mol / L-3 mol / L.
[0034] As a further solution, in step S1, the total mass content of the lithium salt in the polymer electrolyte is selected from 1%-45%.
[0035] As a further solution, in step S1, the total mass content of the lithium salt in the polymer electrolyte is selected from 20%-38%.
[0036] As a further solution, the total mass content of the halogenated amide additive in the polymer electrolyte in step S1 is selected from 0.1% to 5%.
[0037] As a further solution, in step S1, the total mass content of the halogenated amide additive in the polymer electrolyte is selected from 0.5% to 2%.
[0038] As a further solution, in step S1, the total mass content of the monomers containing unsaturated carbon-carbon double bonds and disulfide bonds in the polymer electrolyte is selected from 2% to 10%.
[0039] As a further solution, in step S1, the total mass content of the monomers containing unsaturated carbon-carbon double bonds and disulfide bonds in the polymer electrolyte is selected from 5% to 8%.
[0040] As a further solution, in step S1, the total mass content of the initiator in the polymer electrolyte is selected from 0.1% to 2%.
[0041] As a further solution, in step S1, the total mass content of the initiator in the polymer electrolyte is selected from 0.5% to 1%.
[0042] As a further solution, a halogenated sulfonamide additive may also be added in step S1.
[0043] As a further solution, in step S1, the total mass content of the halogenated sulfonamide additive in the polymer electrolyte is selected from 0.1% to 5%.
[0044] As a further solution, in step S1, the total mass content of the halogenated sulfonamide additive in the polymer electrolyte is selected from 0.5% to 2%.
[0045] As a further solution, in step S2, the dry environment refers to an environment with a water content of less than 1 ppm.
[0046] As a further solution, the ultraviolet light irradiation time is selected from 1 min to 8 min.
[0047] Compared with the prior art, the present invention has at least the following beneficial effects:
[0048] The present invention adopts ether solvent as solvent, which provides a stable environment for the dissolution and conversion of lithium polysulfide. On this basis, by introducing monomers containing unsaturated carbon-carbon double bonds and disulfide bonds, the introduction of additional polymers is avoided, and the occurrence of "shuttle effect" is suppressed; and the addition of halogenated amide additives helps to utilize the compounding effect of monomers containing unsaturated carbon-carbon double bonds and disulfide bonds and halogenated amide additives, further promoting the dissolution and conversion of lithium polysulfide on the basis of suppressing the "shuttle effect", avoiding the consumption of positive and negative active materials; further, by introducing halogenated sulfonamide additives, the cycle performance of lithium-sulfur batteries is further optimized. With the mutual cooperation of ether solvents, monomers containing unsaturated carbon-carbon double bonds and disulfide bonds, and halogenated amide additives, we have obtained the suppression of the "shuttle effect", avoided the consumption of positive and negative active materials, and effectively improved the cycle performance of lithium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0050] Figure 1 This is the state diagram of the polymer electrolyte before and after polymerization;
[0051] Figure 2 This is a comparison chart of the first discharge specific capacity of Example 1 and Comparative Example 1;
[0052] Figure 3 This is a comparison chart of the coulombic efficiency of Example 1 and Comparative Example 1 after 50 cycles;
[0053] Figure 4 Schematic diagram of the dynamic disulfide bond exchange reaction.
[0054] Figure 5 These are Raman spectra of the polymer monomer, the semi-solid electrolyte, and the semi-solid electrolyte with lithium polysulfide (LiPSs) added in Example 1. DETAILED DESCRIPTION
[0055] For ease of understanding, the present invention will be described in more detail below and examples of the present invention are given, but the scope of the present invention is not limited thereby.
[0056] In a first aspect, the present invention provides a gel electrolyte membrane for a lithium-sulfur battery, comprising a base membrane and a polymer electrolyte solidified based on the base membrane, wherein the polymer electrolyte raw materials include a halogenated amide additive, a monomer containing unsaturated carbon-carbon double bonds and disulfide bonds, an ether solvent, a lithium salt, and an initiator.
[0057] In order to suppress the shuttling problem of polysulfide in the electrolyte, we first used ether solvents as solvents, taking advantage of the high solubility of ether solvents for lithium polysulfide to provide a stable environment for the dissolution and conversion of lithium polysulfide. Subsequently, by introducing monomers containing unsaturated carbon-carbon double bonds and disulfide bonds into the polymer electrolyte, we were able to effectively utilize the dynamic exchange reaction of disulfide bonds ( Figure 4 ) interact with lithium polysulfide, thereby inhibiting the shuttling of polysulfide in the electrolyte. Figure 5 As shown in Figure 2, the characteristic Raman peak of disulfide bond SS (~512 cm -1 ), however, after adding LiPSs, the Raman peak of SS disappeared, and the peak at ~534 cm -1 A new S-S8 appeared in the position 2- Raman peaks, which verify the breaking of disulfide bonds in the polymer backbone and the dynamic recombination process with LiPSs. At the same time, monomers containing unsaturated carbon-carbon double bonds and disulfide bonds can further rely on unsaturated carbon-carbon double bonds to polymerize, avoiding the introduction of additional polymers ( Figure 1 ), which largely avoids the loss of positive and negative electrode active materials caused by the introduction of polycarbonate and polyamide monomers. However, relying solely on monomers containing unsaturated carbon-carbon double bonds and disulfide bonds cannot completely avoid the consumption of positive electrode active materials. On the basis of introducing monomers containing unsaturated carbon-carbon double bonds and disulfide bonds, we further introduced halogenated amide additives. On the one hand, we believe that the amide group with strong polarity in the halogenated amide additive can promote the dissolution and conversion of lithium polysulfide by forming hydrogen bonds with the lone pair of electrons of sulfur (S) and forming dipole-dipole interactions with sulfur atoms, thereby preventing the deposition and inactivation of polysulfides caused by the dynamic exchange reaction of disulfide bonds in semi-solid lithium-sulfur batteries; on the other hand, the presence of halogen elements in the halogenated amide additive can also bind to lithium in the battery to form a LiF-rich SEI film at the lithium negative electrode, thereby inhibiting the interfacial side reactions between sulfur-containing polymers and lithium metals, thereby improving the electrochemical performance of lithium-sulfur batteries. With the combined effects of halogenated amide additives, monomers containing unsaturated carbon-carbon double bonds and disulfide bonds, and ether solvents, we have optimized the performance of lithium-sulfur batteries by suppressing the "shuttle effect" while avoiding the consumption of positive and negative active materials.
[0058] On the second aspect, the present solution also proposes an energy storage device using a gel electrolyte membrane as a separator and / or a semi-solid electrolyte.
[0059] As a further solution, the energy storage device includes a battery cell.
[0060] As some preferred schemes, the halogenated amide additive is selected from a chain halogenated amide additive having a terminal amide group and a halogen element substitution number less than or equal to 3. For the halogenated amide additive, the presence of the halogen element can bind to the lithium in the battery to form a LiF-rich SEI film at the lithium negative electrode. When the halogen element substitution number is greater than 3, it may lead to an overly thick or uneven SEI layer, which in turn affects the first coulombic efficiency and first discharge specific capacity of the battery; in addition, we believe that the selection of a chain halogenated amide additive helps to further utilize its chain structure to provide more hydrogen bonds and dipole-dipole interaction sites, strengthen the binding force with polysulfides, and thus optimize the battery cycle performance.
[0061] As a further preferred scheme, the chain halogenated amide additive having a terminal amide group and a halogen element substitution number less than or equal to 3 can be further preferably a chain halogenated amide additive having a carbon chain length less than or equal to 6 and having a terminal amide group and a halogen element substitution number less than or equal to 3.
[0062] As a further preferred embodiment, the carbon chain length may be further preferably 4, and further, the carbon chain length may be further preferably 3, 2, or 1.
[0063] As some preferred non-limiting examples, the chain halogenated amide having a carbon chain length of less than or equal to 4, a terminal amide group and a halogen element substitution number of less than or equal to 3 is selected from trifluoroacetamide Chloroacetamide Iodoacetamide dichloroacetamide Fluoroiodoacetamide Fluorochloroacetamide Chlorofluoroacetamide Bromofluoroacetamide Bromochloroacetamide Any one of .
[0064] As some preferred schemes, the monomer containing unsaturated carbon-carbon double bonds and disulfide bonds is preferably a symmetrical monomer containing double-terminal unsaturated carbon-carbon double bonds and disulfide bonds. The presence of the symmetrical structure helps to construct a more ordered and stable ion channel during the polymerization process, thereby improving the battery's first discharge specific capacity and first-cycle coulombic efficiency. Furthermore, the ordered polymerized polymer can better intercept lithium polysulfide dissolved in the electrolyte, thereby inhibiting the occurrence of the "shuttle effect".
[0065] As some preferred non-limiting examples, the symmetrical monomer containing double terminal unsaturated carbon-carbon double bonds and disulfide bonds can be selected from N, N-bis (acryloyl) cystamine Diallyl disulfide Any one of .
[0066] As a further solution, the polymer electrolyte raw material may further include a halogenated sulfonamide additive.
[0067] Halogenated sulfonamide additives contain halogen elements and sulfonamide functional groups. When the halogenated sulfonamide additives are introduced into the gel electrolyte membrane, firstly, the oxygen in the amino group in the halogenated sulfonamide can act as a hydrogen bond acceptor and interact with the amide group in the halogenated amide additive, thereby affecting the behavior of polysulfide; secondly, the electrophilicity of the halogenated sulfonamide additive itself enables it to act on the polysulfide anion through non-covalent interactions such as ion-dipole interaction, thereby stabilizing the polysulfide and promoting its dissolution; thirdly, the presence of halogen elements in the halogenated sulfonamide additive helps to further interact with the sulfur atoms in the polysulfide and promote the dissociation of the polysulfide; under the joint action of the halogenated sulfonamide additive and the halogenated amide additive, monomers containing unsaturated carbon-carbon double bonds and disulfide bonds, and ether solvents, we further reduced the loss of positive and negative active materials and optimized the cycle efficiency and cycle capacity retention rate.
[0068] As a further preferred solution, the halogenated sulfonamide may be further preferably a chain halogenated sulfonamide with a symmetrical structure, which may provide a more uniform and effective interaction with polysulfides, preventing their uneven distribution and deposition in the electrolyte. At the same time, the symmetrical chain halogenated sulfonamide can also introduce a higher content of halogen elements, thereby further improving the stability of the SEI film and optimizing the battery cycle performance.
[0069] As some preferred non-limiting examples, the chain halogenated sulfonamide having a symmetrical structure may be trifluoromethanesulfonic anhydride. N-Methylbis[(trifluoromethyl)sulfonyl]imide Bis(trifluoromethane)sulfonimide Any one of .
[0070] As a further solution, the ether solvent is selected from any one or more of simple ether solvents, polyether solvents and cyclic ether solvents.
[0071] As a further scheme, the simple ether solvent refers to a solvent having a RO-R' structure, wherein R and R' can be alkyl or aryl groups, and illustratively, can be selected from one or more of diethyl ether, dipropyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, cyclopentyl methyl ether, and 2-methyltetrahydrofuran.
[0072] As a further scheme, the polyether solvent refers to an ether solvent containing multiple ether bonds, usually ethylene glycol units connected by ether oxygen bridges. Exemplarily, it can be selected from one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether, and triethylene glycol diethyl ether.
[0073] As a further embodiment, the cyclic ether solvent refers to one or more of tetrahydrofuran, 1,3-dioxolane, 1,4-dioxane, and tetrahydropyran having a cyclic structure with one or more oxygen atoms in the ring.
[0074] As a further solution, the lithium salt is selected from any one or more of organic lithium salts and inorganic lithium salts.
[0075] As a further embodiment, the organic lithium salt is selected from any one or more of fluorine-substituted lithium sulfonate salts, lithium oxalate salts and lithium borate salts.
[0076] As a further embodiment, the lithium sulfonate salt is selected from any one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium perfluorobutanesulfonate, lithium perfluorobutanesulfonate, lithium bis(trifluoromethanesulfonyl)imide, lithium 1,1,2,2-tetrafluoroethanesulfonate, lithium hexafluoropropanesulfonate, lithium perfluorooctanesulfonate, lithium pentafluorobenzenesulfonate, lithium 1,2,2-trifluoroethanesulfonate, and lithium octafluoropropanesulfonate.
[0077] As a further solution, the lithium borate salt is selected from any one or more of lithium difluorodihydroxyborate, lithium fluoroborate ethoxide, lithium fluoromethyleneborate, and lithium trifluoropropanolborate.
[0078] As a further solution, the inorganic lithium salt is selected from any one or more of fluorine-substituted inorganic lithium borate salts, fluorine-substituted inorganic lithium phosphate salts, fluorine-substituted inorganic lithium chlorate salts, and inorganic lithium nitrate salts.
[0079] As a further embodiment, the fluorine-substituted inorganic lithium borate salt is selected from any one or more of lithium tetrafluoroborate, lithium difluorooxyborate, lithium fluoroborate, lithium trifluoroborate, lithium fluorophosphorus borate, and lithium perfluoropropionate borate.
[0080] As a further embodiment, the fluorine-substituted inorganic lithium phosphate salt is selected from any one or more of fluorolithium phosphate, fluorolithium metaphosphate, bis(fluorooxyphosphoryl)nitrosolithium, fluorolithium phosphite, lithium trifluorophosphate, and lithium hexafluorophosphate.
[0081] As a further embodiment, the fluorine-substituted inorganic lithium chlorate salt is selected from any one or more of lithium perchlorate, lithium difluorochlorate, lithium trifluorochlorate, lithium tetrafluorochlorate, and lithium pentafluorochlorate.
[0082] As a further embodiment, the inorganic lithium nitrate salt is selected from lithium nitrate.
[0083] As a further embodiment, the initiator is selected from any one of ketone compounds and phosphorus oxides.
[0084] As a further embodiment, the ketone compound is selected from any one of 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropanone, benzophenone, and 2-isopropylthioxanthone.
[0085] As a further embodiment, the phosphorus oxide is selected from any one of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, phosphorus trioxide, phosphorus pentoxide, phosphoric anhydride, Na3PO4, phosphorus oxychloride, hypophosphorous acid, and nitrophosphoric acid.
[0086] As a further solution, the polymer electrolyte raw material further includes a second solvent, and the second solvent is selected from any one or more of ester solvents or acetal solvents.
[0087] As a further solution, the ester solvent is selected from any one or more of chain carbonate solvents, carboxylic acid ester solvents, and phosphate ester solvents.
[0088] As a further embodiment, as an even further embodiment, the linear carbonate solvent includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate.
[0089] As a further embodiment, the carboxylic acid ester solvent includes at least one of methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, methyl isobutyrate, ethyl butyrate, methyl trimethylacetate and ethyl trimethylacetate.
[0090] As a further embodiment, the phosphate solvent includes at least one of trimethyl phosphate, triethyl phosphate, tripropyl phosphate, triphenyl phosphate, tris(2,2,2-trifluoroethyl)phosphite and ethoxy(pentafluoro)cyclotriphosphazene.
[0091] As a further solution, the acetal solvent is selected from any one or more of methylal dimethanol, methylal diethanol, acetal dimethanol, acetal diethanol, and 1,1,2,2-tetraethoxyethane.
[0092] As a further solution, the mass ratio of the ether solvent to the second solvent in the gel electrolyte membrane is selected from 0.2 to 2.
[0093] As a further solution, the base film is selected from glass cellulose film, cellulose film and porous polyolefin compound film, and one or more layers of coating can be provided on the base film.
[0094] As a further solution, the porous polyolefin compound membrane is selected from any one of polyethylene porous membrane, polypropylene membrane, polytetrafluoroethylene coated polyolefin membrane, polyvinyl alcohol cross-linked polyolefin membrane, ethylene-propylene copolymer porous membrane, ultra-high molecular weight polyethylene porous membrane, ethylene-vinyl acetate copolymer membrane, polyacrylonitrile coated polyolefin membrane, polyethylene and polylactic acid blended porous membrane, and ethylene-octene copolymer porous membrane.
[0095] As a further solution, the coating is not limited in principle, and for example, can be selected from any one or more of polymer materials, carbon materials, and oxide materials.
[0096] As a further solution, the polymer material is selected from any one or more of polyethylene glycol, polyvinylidene fluoride, polyethylene oxide, polyacrylonitrile, polyurethane, polymethyl methacrylate, polystyrene, and polyvinylidene fluoride-hexafluoropropylene copolymer.
[0097] As a further solution, the carbon material is selected from any one or more of carbon nanotubes, graphene, carbon nanofibers, porous carbon, graphite-like carbon, carbon black, and nitrogen-doped carbon.
[0098] As a further solution, the oxide material is selected from any one or more of Al2O3, zirconium oxide, titanium oxide, silicon oxide, magnesium oxide, tin oxide, yttrium oxide, and cerium oxide.
[0099] As a further solution, the gel electrolyte membrane has a Raman spectrum of 512 cm -1 The Raman scattering peak at comes from SS, and the standard deviation of the peak position is 2 cm -1 Within.
[0100] In a third aspect, the present invention also proposes a method for preparing a gel electrolyte membrane, the specific steps of which are:
[0101] S1: Under an inert atmosphere, a lithium salt is dissolved in an ether solvent, a halogenated amide additive and a monomer containing an unsaturated carbon-carbon double bond and a disulfide bond are added, and then an initiator is added, and the mixture is mixed to obtain a precursor solution;
[0102] S2: In a dry environment, immerse the base film in the precursor solution, take it out after it is completely soaked, and irradiate it with ultraviolet light to obtain a gel electrolyte membrane.
[0103] As a further solution, in step S1, the inert atmosphere is selected from any one of helium, neon, argon, krypton, xenon, and radon.
[0104] As a further solution, in step S1, the total mass content of the lithium salt in the polymer electrolyte is selected from 5% to 50%.
[0105] As a further solution, in step S1, the total mass content of the lithium salt in the polymer electrolyte is selected from 10%-30%.
[0106] As a further solution, in step S1, the concentration of lithium salt is selected from 0.1 mol / L-5 mol / L.
[0107] As a further solution, in step S1, the concentration of lithium salt is selected from 1.5 mol / L-3 mol / L.
[0108] As a further solution, in step S1, the total mass content of the lithium salt in the polymer electrolyte is selected from 1%-45%.
[0109] As a further solution, in step S1, the total mass content of the lithium salt in the polymer electrolyte is selected from 20%-38%.
[0110] As a further solution, the total mass content of the halogenated amide additive in the polymer electrolyte in step S1 is selected from 0.1% to 5%.
[0111] As a further solution, in step S1, the total mass content of the halogenated amide additive in the polymer electrolyte is selected from 0.5% to 2%.
[0112] As a further solution, in step S1, the total mass content of the monomers containing unsaturated carbon-carbon double bonds and disulfide bonds in the polymer electrolyte is selected from 2% to 10%.
[0113] As a further solution, in step S1, the total mass content of the monomers containing unsaturated carbon-carbon double bonds and disulfide bonds in the polymer electrolyte is selected from 5% to 8%.
[0114] As a further solution, in step S1, the total mass content of the initiator in the polymer electrolyte is selected from 0.1% to 2%.
[0115] As a further solution, in step S1, the total mass content of the initiator in the polymer electrolyte is selected from 0.5% to 1%.
[0116] As a further solution, a halogenated sulfonamide additive may also be added in step S1.
[0117] As a further solution, in step S1, the total mass content of the halogenated sulfonamide additive in the polymer electrolyte is selected from 0.1% to 5%.
[0118] As a further solution, in step S1, the total mass content of the halogenated sulfonamide additive in the polymer electrolyte is selected from 0.5% to 2%.
[0119] As a further solution, in step S2, the dry environment refers to an environment with a water content of less than 1 ppm.
[0120] As a further solution, the ultraviolet light irradiation time is selected from 1 min to 8 min.
[0121] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0122] The chemical raw materials involved in the following examples and comparative examples are all prior art and are commercially available. The experimental devices, test devices, etc. involved in the following examples and comparative examples are all conventional devices in the art, without special requirements and limitations.
[0123] Example 1
[0124] Preparation of gel electrolyte membrane
[0125] S1: In an argon-protected glove box, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) with a concentration of 1.5 mol / L and a mass proportion of 22.4% in the electrolyte is dissolved in a mixed solvent of 1,3-dioxolane, ethylene glycol dimethyl ether and methylal dimethanol in a mass ratio of 1:1:1, and a trifluoroacetamide additive of 1% of the total mass of the electrolyte, a total mass of bis(trifluoromethane)sulfonylimide of 1% of the total mass, an N,N-bis(acryloyl)cystamine monomer of 8% of the total mass and a 1-hydroxycyclohexyl phenyl ketone initiator of 1% of the monomer mass are added, and stirring is continued to obtain a precursor solution.
[0126] S2: In an environment with a water content of less than 1 ppm, immerse the polypropylene base film in the precursor solution, take it out after it is completely soaked, and use ultraviolet light for 2 minutes to obtain a gel electrolyte membrane.
[0127] Preparation of batteries
[0128] In an environment with a water content of less than 1 ppm, a gel electrolyte membrane is used as a separator, a sulfur / carbon nanotube / porous carbon material with a mass ratio of 7:2:1 is used as the positive electrode, and lithium metal is used as the negative electrode to assemble a semi-solid lithium-sulfur battery.
[0129] Example 2
[0130] The preparation method is the same as that of Example 1, except that bis(trifluoromethane)sulfonimide is not added.
[0131] Example 3
[0132] The preparation method is the same as that of Example 1, except that trifluoroacetamide is replaced by pentafluoropropionamide.
[0133] Example 4
[0134] The preparation method is the same as that of Example 1, except that the N,N-bis(acryloyl)cystamine monomer is replaced by allyl propyl disulfide.
[0135] Example 5
[0136] The preparation method is the same as that of Example 1, except that bis(trifluoromethane)sulfonyl imide is replaced by trifluoromethanesulfonamide.
[0137] Example 6
[0138] The preparation method is the same as that of Example 1, except that bis(trifluoromethane)sulfonyl imide accounts for 0.1% of the total mass of the electrolyte.
[0139] Example 7
[0140] The preparation method is the same as that of Example 1, except that the N,N-bis(acryloyl)cystamine monomer accounts for 4% of the total mass of the electrolyte.
[0141] Example 8
[0142] The preparation method is the same as that of Example 1, except that trifluoroacetamide accounts for 3% of the total mass of the electrolyte.
[0143] Example 9
[0144] The preparation method is the same as that of Example 1, except that the concentration of LiTFSI is 2 mol / L, and its mass proportion in the electrolyte is 27.8%.
[0145] Example 10
[0146] The preparation method is the same as that of Example 1, except that the UV curing time is 5 minutes.
[0147] Embodiment 11
[0148] The preparation method is the same as that of Example 1, except that the polypropylene base film is replaced by a polypropylene film coated with Al2O3.
[0149] Comparative Example 1
[0150] The preparation method is the same as that of Example 1, except that trifluoroacetamide is not added.
[0151] Comparative Example 2
[0152] The preparation method is the same as that of Example 1, except that N,N-bis(acryloyl)cystamine is not added.
[0153] Comparative Example 3
[0154] The preparation method is the same as that of Example 1, except that ethylene glycol dimethyl ether is not added.
[0155] Comparative Example 4
[0156] The preparation method is the same as that of Example 1, except that lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) with a concentration of 1 mol / L and a mass proportion of 16% in the electrolyte is dissolved in a mixed solvent of 1,3-dioxolane and ethylene glycol dimethyl ether with a mass ratio of 1:1 as a liquid electrolyte instead of the precursor solution.
[0157] Comparative Example 5
[0158] The preparation method is the same as that of Example 1, except that the preparation is carried out by in-situ thermal polymerization, that is, the precursor solution is injected into the battery, and the battery is assembled and heated at 60° C. for 3 hours.
[0159] The test conditions of Examples 1-11 and Comparative Examples 1-5 are shown in Table 1.
[0160] Test method: Lithium-sulfur batteries were tested for constant current charge and discharge cycles at 25°C, within the charge and discharge voltage range of 2.8 to 1.2V, and at a rate of 0.2C.
[0161] First discharge specific capacity = first discharge capacity / mass of active sulfur
[0162] First coulombic efficiency = (first discharge capacity / first charge capacity) * 100%
[0163] 50-cycle capacity retention rate = (50th discharge capacity / first discharge capacity) * 100%
[0164] 50th coulombic efficiency = (50th discharge capacity / 50th charge capacity)*100%
[0165] Raman spectroscopy test
[0166] Labram HR was used to test the Raman spectrum, and the test wavelength was 532nm.
[0167] The test results of Examples 1-11 and Comparative Examples 1-5 are shown in Table 2.
[0168] Table 1
[0169]
[0170]
[0171]
[0172] Table 2
[0173]
[0174]
[0175] From Examples 1-11 and Comparative Examples 1-5, it can be observed that Examples 1-11 as a whole exhibit higher first discharge specific capacity and first cycle coulombic efficiency than Comparative Examples 1-5, indicating that the gel electrolyte membrane can ensure higher ion conductivity in the battery. After 50 cycles, Examples 1-11 as a whole still exhibit better cycle capacity retention and coulombic efficiency than Comparative Examples 1-5, indicating that the gel electrolyte membrane can effectively suppress the "shuttle effect" while avoiding the loss of positive and negative active materials, thereby effectively optimizing the cycle performance of the lithium-sulfur battery.
[0176] From Example 1 and Comparative Examples 1-3, it can be observed that ( Figure 2-Figure 3 ), whether it is a halogenated amide additive, a monomer containing unsaturated carbon-carbon double bonds and disulfide bonds, or an ether solvent, it plays an important role in improving the ionic conductivity of lithium-sulfur batteries, inhibiting the "shuttle effect", and avoiding the consumption of positive and negative electrode active materials. In Comparative Examples 1-3, when there is a lack of halogenated amide additives and monomers containing unsaturated carbon-carbon double bonds and disulfide bonds, Comparative Examples 1-2 show a lower 50-time capacity retention rate and 50th coulomb efficiency than when there is a lack of ether solvents. This may be because in the gel electrolyte membrane, monomers containing unsaturated carbon-carbon double bonds and disulfide bonds are required to work synergistically with halogenated amide additives. While using monomers containing unsaturated carbon-carbon double bonds and disulfide bonds to inhibit the "shuttle effect", halogenated amide additives are used to activate polysulfides to avoid the loss of positive and negative electrode active materials. Therefore, Example 1 shows a cycle capacity far superior to that of Comparative Examples 1-2 ( Figure 3 ). In addition, the addition of monomers containing unsaturated carbon-carbon double bonds and disulfide bonds can also utilize the self-polymerization of monomers containing unsaturated carbon-carbon double bonds and disulfide bonds to construct efficient ion channels. When the monomers containing unsaturated carbon-carbon double bonds and disulfide bonds are missing, Comparative Example 2 exhibits a lower first discharge specific capacity and first cycle coulombic efficiency than Comparative Example 1. In Comparative Example 3, we observed that when no ether solvent was added as a solvent, the overall performance of Comparative Example 3 was greatly affected. This may be because the lack of ether solvents may cause the solubility of lithium polysulfide to decrease, so the first coulombic efficiency and specific capacity of Comparative Example 3 are affected. In the subsequent cycle, although the presence of halogenated amide additives, monomers containing unsaturated carbon-carbon double bonds and disulfide bonds, and halogenated sulfonamide additives can optimize the cycle capacity of lithium-sulfur batteries to a certain extent, the lack of ether solvents may not provide a stable environment for the dissolution and conversion of lithium polysulfide, so the cycle capacity is also affected.
[0177] Comparative Example 4 uses an electrolyte instead of a gel electrolyte. It can be clearly observed from Comparative Example 4 that, compared with Example 1, the first discharge specific capacity and coulombic efficiency of Comparative Example 4 are affected. This may be because the serious dissolution and shuttle effect of polysulfides in the liquid electrolyte leads to a serious loss of active substances. The use of a gel electrolyte can effectively alleviate the shuttle effect of polysulfides. Therefore, Example 1 exhibits better first discharge specific capacity and first cycle coulombic efficiency than Comparative Example 4.
[0178] Example 1 and Comparative Example 5 demonstrate the effect of polymerization methods on the performance of lithium-sulfur batteries. When comparative example 5 is prepared by in-situ thermal polymerization, it can be observed that the first discharge specific capacity of comparative example 5 is only 735.8 mAh / g, the first cycle coulombic efficiency is only 55.2%, and after 50 cycles, the capacity retention rate of comparative example 5 is only 75.2%, and the coulombic efficiency of the 50th cycle is only 78.5%, both lower than that of Example 1. This may be because when UV curing is not used for curing, monomers containing unsaturated carbon-carbon double bonds and disulfide bonds may not be fully polymerized to construct a complete and stable ion-conducting pathway, nor can the dynamic exchange reaction of disulfide bonds be fully utilized to inhibit the shuttling of polysulfides in the electrolyte. At the same time, during the in-situ thermally initiated polymerization process, the monomers that are not fully polymerized have more lone pairs of electrons, which are very likely to produce interfacial side reactions with lithium metal, thereby deteriorating the battery performance.
[0179] Examples 1 and 2 demonstrate the compounding effect of halogenated sulfonamide additives in gel electrolyte membranes. When halogenated sulfonamide additives are added, Example 1 exhibits a higher cycle capacity retention rate and 50th coulombic efficiency than Example 2. This may be because the amino group in the sulfonamide group can interact with the amide group, thereby affecting the behavior of polysulfides; secondly, the electrophilicity of the halogenated sulfonamide additive itself enables it to stabilize polysulfides through non-covalent interactions with polysulfide anions and promote the dissolution of polysulfides; in addition, the presence of halogen elements in halogenated sulfonamide also helps to promote the dissociation of polysulfides. Under the compounding effect of halogenated sulfonamide additives, Example 1 exhibits good capacity retention rate (84.3%) and 50th coulombic efficiency (89.6%).
[0180] Examples 1 and 3 demonstrate the effects of halogenated amide additives with different structures on the performance of the gel electrolyte membrane. It can be observed from Example 1 that when trifluoroacetamide is used as an additive, Example 1 exhibits better first cycle capability and first discharge specific capacity than Example 3. This may be because the SEI film constructed with the participation of fluorine element in trifluoroacetamide is more appropriately thick than the SEI film constructed with the participation of pentafluoroacetamide, which can improve the first discharge specific capacity and first cycle coulombic efficiency of the battery while protecting the battery. Therefore, Example 1 exhibits better electrochemical performance than Example 3.
[0181] Examples 1 and 4 show the effects of monomers containing unsaturated carbon-carbon double bonds and disulfide bonds of different structures on the performance of gel electrolyte membranes. When N, N-bis(acryloyl)cystamine is used as an additive, Example 1 shows better first discharge specific capacity and first cycle coulombic efficiency than Example 4. After 50 cycles, Example 1 also shows better cycle capacity retention and 50th coulombic efficiency. This may be because, compared with allyl propyl disulfide, N, N-bis(acryloyl)cystamine with a symmetrical structure and double-terminal unsaturated carbon-carbon double bonds can bind to the basement membrane during the polymerization process to construct a more uniform and ordered ion channel, and at the same time construct a more uniform disulfide interception network to fully inhibit the "shuttle effect", so Example 1 shows better cycle ability.
[0182] Examples 1 and 5 demonstrate the effect of the structure of halogenated sulfonamide on battery performance. When the halogenated sulfonamide used is a symmetrical chain halogenated sulfonamide, Example 1 exhibits better first discharge specific capacity and first cycle coulombic efficiency than Example 5, and exhibits better cycling ability in subsequent cycles. This may be because the symmetrical chain halogenated sulfonamide may provide more uniform and effective interaction with polysulfides, while providing a higher content of halogen elements, thereby optimizing battery performance.
[0183] Examples 1 and 6-9 demonstrate the effects of the proportions of halogenated amide additives, monomers containing unsaturated carbon-carbon double bonds and disulfide bonds, and halogenated sulfonamide additives in the electrolyte and the concentration of lithium salt on battery performance. It can be observed from Examples 6-9 that the proportions of halogenated amide additives, monomers containing unsaturated carbon-carbon double bonds and disulfide bonds, and halogenated sulfonamide additives in the electrolyte and the concentration of lithium salt should be controlled and coordinated with each other. The reason why Example 1 can show the effects of Examples 6-9 is that the addition amount of each component in Example 1 can give full play to the compounding effect of each other, thereby optimizing battery performance.
[0184] Examples 1 and 10 show the effect of UV curing time on battery performance. It can be observed that when UV curing is 2 minutes, Example 1 shows a better first discharge specific capacity than Example 10, and Example 10 shows better cycle capacity retention and coulombic efficiency after 50 cycles. This may be because a longer curing time will increase the degree of polymerization of monomers containing unsaturated carbon-carbon double bonds and disulfide bonds, thereby improving the ability to inhibit the "shuttle effect". At the same time, when cured for 2 minutes, Example 1 has a higher ionic conductivity, so the first discharge specific capacity and the first cycle coulombic efficiency are better.
[0185] Examples 1 and 11 discussed the influence of the base film. It can be observed that both Example 1 and Example 11 have better initial discharge capacity and cycle performance, indicating that different base films uniformly show good effects.
[0186] The technical features of the above-described embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. Although the embodiments of the present invention have been shown and described above, it can be understood that the above-described embodiments are exemplary and cannot be understood as limitations of the present invention. Those of ordinary skill in the art can change, modify, replace and deform the above-described embodiments within the scope of the present invention. In addition, those of ordinary skill in the art can combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.
Claims
1. A gel electrolyte membrane for lithium-sulfur battery, characterized in that: The gel electrolyte membrane includes a base film and a polymer electrolyte cured based on the base film. The gel electrolyte membrane has a Raman spectrum of 512 cm -1 The Raman scattering peak at comes from SS, and the standard deviation of the peak position is 2 cm -1 Within.
2. The gel electrolyte membrane according to claim 1, characterized in that The polymer electrolyte raw materials include halogenated amide additives, monomers containing unsaturated carbon-carbon double bonds and disulfide bonds, ether solvents, lithium salts, and initiators.
3. The gel electrolyte membrane according to claim 2, characterized in that: The halogenated amide additive is selected from a chain halogenated amide additive having a terminal amide group and a halogen element substitution number of less than or equal to 3; Preferably, the carbon chain length of the chain halogenated amide additive having a terminal amide group and a halogen element substitution number of 3 or less is less than or equal to 6; Preferably, the carbon chain length of the chain halogenated amide additive having a terminal amide group and a halogen element substitution number of less than or equal to 3 is less than or equal to 4; Preferably, the chain halogenated amide having a carbon chain length of less than or equal to 4, a terminal amide group and a halogen element substitution number of less than or equal to 3 is selected from trifluoroacetamide Chloroacetamide Iodoacetamide Dichloroacetamide Fluoroiodoacetamide Fluorochloroacetamide Chlorofluoroacetamide Bromofluoroacetamide Bromochloroacetamide Any one of; The monomer containing unsaturated carbon-carbon double bonds and disulfide bonds is preferably a symmetrical monomer containing double-terminal unsaturated carbon-carbon double bonds and disulfide bonds; Preferably, the symmetrical monomer containing a double-terminal unsaturated carbon-carbon double bond and a disulfide bond can be selected from N,N-bis(acryloyl)cystamine Diallyl disulfide Any one of .
4. The gel electrolyte membrane according to claim 2, characterized in that: The polymer electrolyte raw material may also include a halogenated sulfonamide additive; The halogenated sulfonamide may further preferably be a chain halogenated sulfonamide having a symmetrical structure; Preferably, the chain halogenated sulfonamide with a symmetrical structure is selected from trifluoromethanesulfonic anhydride N-Methylbis[(trifluoromethyl)sulfonyl]imide Bis(trifluoromethane)sulfonimide Any one of .
5. The gel electrolyte membrane according to claim 2, characterized in that: The ether solvent is selected from any one or more of simple ether solvents, polyether solvents and cyclic ether solvents.
6. The gel electrolyte membrane according to claim 2, characterized in that: The lithium salt is selected from any one or more of organic lithium salts and inorganic lithium salts; Preferably, the organic lithium salt is selected from any one or more of fluorine-substituted lithium sulfonate salts, lithium oxalate salts and lithium borate salts; Preferably, the inorganic lithium salt is selected from any one or more of fluorine-substituted inorganic lithium borate salts, fluorine-substituted inorganic lithium phosphate salts, fluorine-substituted inorganic lithium chlorate salts, and inorganic lithium nitrate salts; Preferably, the initiator is selected from any one of ketone compounds and phosphorus oxides; Preferably, the polymer electrolyte raw material further includes a second solvent, and the second solvent is selected from any one or more of an ester solvent or an acetal solvent.
7. The gel electrolyte membrane according to claim 6, characterized in that: The ester solvent is selected from any one or more of a chain carbonate solvent, a carboxylic acid ester solvent, and a phosphate ester solvent; Preferably, the mass ratio of the ether solvent to the second solvent in the gel electrolyte membrane is selected from 0.2 to 2; Preferably, the base film is selected from glass cellulose film, cellulose film and porous polyolefin compound film; The base film may be provided with one or more coating layers.
8. A method for preparing a gel electrolyte membrane, characterized in that: The specific steps for preparing the gel electrolyte membrane are: S1: Under an inert atmosphere, a lithium salt is dissolved in an ether solvent, a halogenated amide additive and a monomer containing an unsaturated carbon-carbon double bond and a disulfide bond are added, and then an initiator is added, and the mixture is mixed to obtain a precursor solution; S2: In a dry environment, immerse the base film in the precursor solution, take it out after it is completely soaked, and irradiate it with ultraviolet light to obtain a gel electrolyte membrane.
9. The method for preparing a gel electrolyte membrane according to claim 8, characterized in that: In step S1, the inert atmosphere is selected from any one of helium, neon, argon, krypton, xenon, and radon; Preferably, in step S1, the total mass content of the lithium salt in the polymer electrolyte is selected from 5% to 50%; Preferably, in step S1, the total mass content of the lithium salt in the polymer electrolyte is selected from 10% to 30%; Preferably, in step S1, the lithium salt concentration is selected from 0.1 mol / L-5 mol / L; Preferably, in step S1, the lithium salt concentration is selected from 1.5 mol / L-3 mol / L; Preferably, in step S1, the total mass content of lithium salt in the polymer electrolyte is selected from 1%-45%; Preferably, in step S1, the total mass content of lithium salt in the polymer electrolyte is selected from 20%-38%; Preferably, the total mass content of the halogenated amide additive in the polymer electrolyte in step S1 is selected from 0.1% to 5%; Preferably, the total mass content of the halogenated amide additive in the polymer electrolyte in step S1 is selected from 0.5% to 2%; Preferably, in step S1, the total mass content of the monomers containing unsaturated carbon-carbon double bonds and disulfide bonds in the polymer electrolyte is selected from 2% to 10%; Preferably, in step S1, the total mass content of the monomers containing unsaturated carbon-carbon double bonds and disulfide bonds in the polymer electrolyte is selected from 5% to 8%; Preferably, in step S1, the total mass content of the initiator in the polymer electrolyte is selected from 0.1% to 2%; Preferably, in step S1, the total mass content of the initiator in the polymer electrolyte is selected from 0.5% to 1%; Preferably, a halogenated sulfonamide additive may also be added in step S1; Preferably, in step S1, the total mass content of the halogenated sulfonamide additive in the polymer electrolyte is selected from 0.1% to 5%; Preferably, in step S1, the total mass content of the halogenated sulfonamide additive in the polymer electrolyte is selected from 0.5% to 2%; In step S2, the dry environment refers to an environment with a water content of less than 1 ppm; Preferably, in step S2, the ultraviolet light irradiation time is selected from 1 min to 8 min.
10. Any one of an electrode assembly, a battery cell, and an energy storage device having the gel electrolyte membrane according to any one of claims 1 to 7 or the gel electrolyte membrane obtained by the method for preparing a gel electrolyte membrane according to any one of claims 8 to 9.
Citation Information
Patent Citations
Preparation method of modified diaphragm-electrolyte integrated solid electrolyte and battery
CN113540575A
Self-repairing polymer electrolyte capable of realizing in-situ thermal polymerization and preparation method of self-repairing polymer electrolyte
CN113964380A
Preparation method of deep eutectic solvent doped polyvinylidene fluoride solid electrolyte
CN118970166A
Cited By
Modified phosphate flame-retardant additive for enhancing thermal stability and application of modified phosphate flame-retardant additive
CN120464023A
Composite amphoteric cellulose solid electrolyte membrane, method for preparing the same, use thereof, and secondary battery
CN122511992A